To Determine Mortality Among Earlier Children Of Multigravida Women (Journal of Pharmaceutical Negative Results, 2023)
Background: Children are a future of nation and take precaution of child health it’s our responsibility. Multigravida women etiological factors more much affect on children health. But these factors affect on children heath at the time of pregnancy to birth of children and after that see the effect on children growth and development in living life sometime chance to child suffering any kind of morbidity and its cause to die.Objective: To determine mortality among earlier children of multigravida women.Methodology: The present descriptive cross-sectional study was use. The study conducted on multigravida women randomly sample of a village from selected PHCs. total 492 multigravida women with her earlier children age 0-18 yrs age group was enrolled. To conduct this study, a predesigned Structured Interview questionnaire was developed and all the questions were framed keeping the study objectives in mind to obtain the necessary information.Result: out of 492 multigravida women 21(2.1%) were having earlier children mortality. majority woman was gravida 2nd and Para one women and gravida 3rd Para two.Conclusion and recommendation: The regrettable side to the issue is that most of the mortality are largely preventable by simple interventions like; Promotion of hygienic practices, through proper health education to their parents. Community health workers should also be trained adequately so that they are able to pick up signs of illness and encourage people in the community to seek treatment and reduced mortality in children.